Enhancing the employee engagement : the mediating role of exchange ideology - Lianto; Anis Eliyana; Fauzan, Rizky (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study analyses a model that links three predictors namely workplace spirituality, self-efficacy, and person-organization fit to employee engagement through the mediating role of exchange ideology. Drawing on social exchange theory, researchers expected that exchange ideology would mediate the relationship between the given antecedents and employee engagement. This study used quantitative method to collect data and WarpPLS5.0 to analyze the data. The results of a survey conducted among 100 employees of credit unions in West Kalimantan, Indonesia, indicated that employees with stronger spirituality, self-efficacy, and values compatibility engaged better at work. Researchers also found that exchange ideology did not mediate the relationship between workplace spirituality and employee engagement although the exchange ideology mediated the relationship between two predictors namely self-efficacy and person-organization fit to employee engagement.